2015
DOI: 10.17578/19-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Equity Anomalies and Idiosyncratic Risk Around the World

Abstract: In this study, we examine how idiosyncratic risk is correlated with a wide array of anomalies,including asset growth, book-to-market, investment-to-assets, momentum, net stock issues, size, and total accruals, in international equity markets. We use zero-cost trading strategy and multifactor models to show that these anomalies produce significant abnormal returns. The abnormal returns vary dramatically among different countries and between developed and emerging countries. We provide strong evidence to support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Then, the CAPM and the model of Fama and French (1993) cannot capture the momentum return. Our results are consistent with those found by Zoghlami (2011) in the Tunisian equity market and Fan et al (2015) in most of the 34 stock markets studied. Table (2) also displays that for the most beneficial 6-month/6-month strategy, the beta(a measure of the systematic risk) of the winner portfolio is more than the beta of the loser portfolio in the CAPM and the three factors model of Fama and French (1993).…”
Section: Evidence Of Abnormal Returnssupporting
confidence: 93%
See 1 more Smart Citation
“…Then, the CAPM and the model of Fama and French (1993) cannot capture the momentum return. Our results are consistent with those found by Zoghlami (2011) in the Tunisian equity market and Fan et al (2015) in most of the 34 stock markets studied. Table (2) also displays that for the most beneficial 6-month/6-month strategy, the beta(a measure of the systematic risk) of the winner portfolio is more than the beta of the loser portfolio in the CAPM and the three factors model of Fama and French (1993).…”
Section: Evidence Of Abnormal Returnssupporting
confidence: 93%
“…Zoghlami (2011) also found that the three factors model of Fama and French (1993) are unable to justify the momentum profitability in the Tunisian market for the period 1998-2004. Fan et al (2015) documented that the three factors model of Fama and French (1993) is inept to fully capture the momentum profitability in most of the 43 stock markets studied between 1981 and 2009.…”
Section: Explanations Of the Momentum Returnsmentioning
confidence: 99%
“…Literature on the value-growth phenomenon has shed light to two key explanations, risk and behavioral biases. A bulk of studies have associated the value premium with measures of risk, such as the standard deviation of returns, or of analyst forecasts and idiosyncratic volatility (Athanassakos 2009, Ang and Chen 2007, Vassalou and Xing 2004, Adrian and Franzoni 2005, Lewellen and Nagel 2006, Petkova and Zhang 2005, Doukas, Kim and Pantzalis 2004, Athanassakos 2011, Ackert and Athanassakos 1997, Li, Brooks and Miffre 2009, Fan, Opsal and Yu 2015, Guo, Savickas, Wang and Yang 2009, Cao 2015, Hou and Loh 2016. A parallel stream of literature associates the value premium with errors in expectations, as investors may be too optimistic for growth relative to value stocks (seminal paper, Lakonishok, et al 1994).…”
Section: Related Literature and Formation Of Expectationsmentioning
confidence: 99%
“…Analyst uncertainty, reflected either in higher dispersion of analyst forecasts or higher absolute forecast errors, is likely to increase the perception of investment risk and consequently the required rate of return. 8 Consistent with prior research (i.e., Fan, Opsal and Yu 2015, Guo, Savickas, Wang and Yang 2009, Lewellen and Nagel 2006, we measure idiosyncratic volatility (IVol) using the standard deviation of daily abnormal stock returns during the fiscal year. We obtain abnormal returns as the residuals from regressing the company's daily stock returns adjusted for the risk free rate on the market premium.…”
Section: Risk and Behavioral Factorsmentioning
confidence: 99%
“…Idiosyncratic risk accounts for a large proportion of firms' total risks (Goyal and Santa-Clara, 2003;Gaspar and Massa, 2006) and is an essential factor affecting stock returns. High idiosyncratic volatility indicates that the guiding role of the stock price on capital flow is relatively weak and that the capital market may have defects in resource allocation (Bansal and Clelland, 2004;Fan et al, 2015;Hu et al, 2020). Prior research results show that up to standard information disclosure contributes to the reduction in the degree of investors' cognitive divergence on stock value, thus improving the pricing efficiency of the market model and reducing the stock idiosyncratic volatility (Jiang et al, 2009;Lee and Liu, 2011;Ziegler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%